2021
DOI: 10.1111/camh.12457
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, depressive symptoms, and digital self‐harm among adolescents

Abstract: Background This study examines the relationship between sleep duration, depression, and engagement in a novel cyber behavior, digital self‐harm, among adolescents. Method Logistic regression analyses were conducted using cross‐sectional data from the 2019 Florida Youth Substance Abuse Survey (N = 9,819; 48% male; avg. grade level = 9th grade [SD = 1.9]) to analyze the association between sleep duration and digital self‐harm. A Karlson–Holm–Breen (KHB) analysis was used to assess whether depressive symptoms att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The prevalence of digital self‐harm found in the current work is in line with that found in previous studies based on both localized samples and national data (Englander, 2013; Erreygers et al., 2020; Meldrum et al., 2022; Pacheco et al., 2019; Patchin & Hinduja, 2017; Semenza et al., 2022). The rate of suicidal thoughts and attempts within our sample of middle and high schoolers across America are lower than what was observed in the Youth Risk Behavior Surveillance Survey in 2019 (referenced above), but the latter does not measure suicidality among middle schoolers and as such would expectedly include higher percentages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of digital self‐harm found in the current work is in line with that found in previous studies based on both localized samples and national data (Englander, 2013; Erreygers et al., 2020; Meldrum et al., 2022; Pacheco et al., 2019; Patchin & Hinduja, 2017; Semenza et al., 2022). The rate of suicidal thoughts and attempts within our sample of middle and high schoolers across America are lower than what was observed in the Youth Risk Behavior Surveillance Survey in 2019 (referenced above), but the latter does not measure suicidality among middle schoolers and as such would expectedly include higher percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Among the findings from this small but growing body of research, approximately 5%–10% of youth report having engaged in digital self‐harm, and both bullying victimization and depressive symptoms are correlated with participation (Englander, 2013; Erreygers et al., 2020; Meldrum, Patchin, Young, & Hinduja, 2022; Pacheco, Melhuish, & Fiske, 2019; Patchin & Hinduja, 2017; Semenza, Meldrum, Testa, & Jackson, 2022). Relatedly, digital self‐harm is positively associated with physical self‐harm (Erreygers et al., 2020; Patchin & Hinduja, 2017), a concerning fact given that the latter occurs at a rate between 7.5% and 46.5% among adolescents according to a recent systematic review (Cipriano, Cella, & Cotrufo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…FOV sharing a common causal pathway with physical self-harm is further supported by the work of Semenza et al [13], who also analysed data from Florida highschoolers. Using logistic regression, it was found that FOV was negatively associated with sleep duration, which is also an established predictor of physical self-harm.…”
Section: Introductionmentioning
confidence: 78%
“…This item had four response categories ranging from 1 = strongly disagree to 4 = strongly agree . Sleep has been related to well-being and depression stress (Ndung’u Muring’u et al, 2021; Semenza et al, 2022).…”
Section: Methodsmentioning
confidence: 99%